Randomized clinical trial of surgical vs. percutaneous vs. hybrid revasculatization in multivessel coronary artery disease: 3 years follow-up (the HREVS Trial). (25th November 2020) - Ganyukov, V; Kochergin, N; Shilov, A; Tarasov, R; Skupien, J; Szot, W; Kokov, A; Popov, V; Kozyrin, K; Barbarash, O; Barbarash, L; Musialek, P
Abstract: Aim: Optimal revascularization strategy in multi-vessel (MV) coronary artery disease (CAD) eligible for percutaneous intervention (PCI) and surgery remains unresolved. We evaluated, in a randomized clinical trial, residual myocardial ischemia (RI) and clinical outcomes of MV-CAD revascularization using coronary artery bypass grafting (CABG), hybrid coronary revascularization (HCR) or MV-PCI. Materials and methods: Consecutive MV-CAD patients (n=155) were randomized (1:1:1) to conventional CABG (LIMA-LAD plus venous grafts) or HCR (MIDCAB LIMA-LAD followed by PCI for remaining vessels) or MV-PCI (everolimus-eluting CoCr stents) under Heart Team agreement on equal technical and clinical feasibility of each strategy. The primary endpoint was SPECT at 12 months (primary endpoint of RI that the trial was powered for; a measure of revascularization mid-term efficacy and an independent predictor of long-term prognosis). The secondary endpoint was 3-year MACCE. Results: Baseline characteristics were similar between the study arms. 5 (9.8%) patients in the HCR group required conversion to CABG. Data are given respectively for the CABG, HCR and MV-PCI arm. Incomplete revascularization rate was 8.0% vs. 7.7% vs. 5.7% (p=0.86). At 12 months, RI was 5 (2, 9)% vs. 5 (3, 7)% vs. 6 (3, 10)% (median; Q1, Q3) with non-inferiority p values of 0.0006 (HCR vs. CABG) and 0.016 (MV-PCI vs. CABG). 3-year MACCE rate was similar (34.7% vs. 27.1% vs. 38%; p=0.18). Conclusion: In patients with MV-CAD amenable to CABG, HCR, and MV-PCI, endpoints of residual myocardial ischemia at 12 months and 3-year MACCE were similar. ClinicalTrials: gov identifier: NCT01699048 Funding Acknowledgement: Type of funding source: None